A low-density anhydrous ferric phosphate and a method for producing the same
Patent Information
- Application Number
- CN202611059680.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-16
AI Technical Summary
但研磨效率与无水磷酸铁粉末状态等相关,一方面,磷酸铁具有很强的晶格强度,导致材料宏观硬度较大,研磨效率低,对研磨机器的损耗较大,极大增加了时间和能耗成本;另一方面,磷酸铁锂正极材料仅对研磨后的无水磷酸铁具有继承性,研磨后的无水磷酸铁也决定了磷酸铁锂正极材料的电化学性能
(1)本发明的无水磷酸铁,其颗粒具有较低的致密度,其片状一次颗粒较薄,更易于研磨,能够提高后续磷酸铁锂合成时的研磨加工效率;
Smart Images

Figure CN122916080A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery cathode material precursor technology, and specifically relates to a low-density anhydrous iron phosphate and its preparation method. Background Technology
[0002] Lithium iron phosphate (LFP) batteries offer higher safety and lower cost advantages compared to ternary lithium batteries. They also boast advantages such as good thermal stability, long cycle life, environmental friendliness, and abundant raw material sources, making them the most promising cathode material for power lithium-ion batteries and gaining increasing favor among automakers. Currently, most LFP preparation processes employ a solid-state method, sintering anhydrous iron phosphate with lithium salts.
[0003] To ensure the performance of subsequent lithium iron phosphate materials, the iron phosphate needs to be thoroughly ground to guarantee complete reaction. However, grinding efficiency is related to the state of the anhydrous iron phosphate powder. On the one hand, iron phosphate has a very strong lattice strength, resulting in high macroscopic hardness, low grinding efficiency, and significant wear and tear on the grinding machine, greatly increasing time and energy costs. On the other hand, lithium iron phosphate cathode materials only inherit the properties of ground anhydrous iron phosphate, and the ground anhydrous iron phosphate also determines the electrochemical performance of the lithium iron phosphate cathode material.
[0004] Therefore, there is a need to provide an anhydrous iron phosphate that is low in density, easy to grind, and can improve grinding efficiency. This anhydrous iron phosphate has high density and specific surface area after grinding, so as to ensure that a lithium iron phosphate cathode material with better performance can be obtained in the future. Summary of the Invention
[0005] The present invention aims to at least solve one of the technical problems existing in the related art. To this end, the present invention proposes a low-density anhydrous ferric phosphate and its preparation method. The anhydrous ferric phosphate has the characteristics of low density and easy grinding, and has high density and specific surface area after grinding.
[0006] The above-mentioned technical objective of the present invention is achieved through the following technical solution: A low-density anhydrous ferric phosphate is composed of secondary particles formed by the agglomeration of primary particles. The secondary particles have a particle size D50 of 2-10 μm, and the primary particles are plate-like with a thickness d of 0.05-0.15 μm. The loose bulk density ρ1 of the secondary particles is 0.4-0.7 g / cm³, and the specific surface area S1 is 2.0-10.5 m². 2 / g.
[0007] In one embodiment, after the low-density anhydrous ferric phosphate is ground to a D50' of 0.4-0.6 μm, the resulting material has a specific surface area S2 of 12-22 m² / g and a loose packing density ρ2 of 0.45-0.75 g / cm³.
[0008] In one embodiment, the low-density anhydrous ferric phosphate, before and after grinding, satisfies the following relationship: K1 is the grinding coefficient, with a value ranging from 15.0 to 30.0 m. 2 / g.
[0009] In one embodiment, the low-density anhydrous ferric phosphate, before and after milling, satisfies the following relationship: K2 is the synthesis coefficient, with a value ranging from 7.5 to 11.0 μm. -1 .
[0010] In one embodiment, the low-density anhydrous ferric phosphate, before and after milling, satisfies the following relationship: W is the processing coefficient, with a value ranging from 70.0 to 115.0 m. 2 / g.
[0011] In one embodiment, the method for grinding the low-density anhydrous ferric phosphate to a D50' of 0.4-0.6 μm is as follows: ① Take 100g of anhydrous ferric phosphate in 4 portions, add 150mL of deionized water to each portion, and mix to make 4 slurries; ② Take 4 portions of 800g zirconium oxide balls with a large ball diameter of 1mm and a small ball diameter of 0.5mm, and a mass ratio of 1:1; ③ The above materials are loaded into the four tanks of a planetary four-cylinder grinder with a motor power of 1.5kW and a capacity of 2L (500mL per tank × 4 tanks); ④ Start the grinder, adjust the speed to 300 r / min, grind for 30 minutes, stop and cool for 10 minutes, repeat 8 times; ⑤ After grinding, separate the zirconia balls to obtain a slurry; ⑥ The slurry is filtered to obtain a solid, which is then dried at 100°C for 2 hours and refilled into the grinding mill along with the zirconia balls; ⑦ Start the grinder, adjust the speed to 200 r / min, grind for 20 min, and then separate to obtain the ground anhydrous ferric phosphate product.
[0012] The above is only one method for grinding anhydrous ferric phosphate to a D50' of 0.4-0.6μm. Other grinding methods can also be used to obtain anhydrous ferric phosphate grinding products with a D50' of 0.4-0.6μm. This method does not limit the scope of protection of this patent.
[0013] A method for preparing low-density anhydrous ferric phosphate as described above includes the following steps: (1) Mix ferric salt with phosphate, and then add acid to prepare a ferric phosphate solution with a pH of -1.0 to 0.5; (2) Using the phosphorus iron solution obtained in step (1) as the base liquid, add alkaline solution to adjust the pH to 1.8-2.2, then add N-nitrosophenylammonium solution, and heat to carry out the reaction. Then, separate the solid and liquid, and calcine the obtained solid phase once in an oxygen atmosphere to obtain the calcined material. (3) After mixing and soaking the calcined material obtained in step (2) with ammonium phosphate solution, the solid and liquid are separated, and the obtained solid phase is calcined a second time in an oxygen atmosphere to obtain low-density anhydrous iron phosphate.
[0014] In one embodiment, step (1) includes at least one of the following features: Feature 1: The molar ratio of iron to phosphorus in the phosphorus-iron solution is 1:(1.02-1.05); Feature 2: The iron ion concentration in the phosphorus-iron solution is 0.1-2.0 mol / L; Feature 3: The ferric salt is at least one of ferric sulfate, ferric chloride, and ferric nitrate; Feature 4: The phosphate is at least one of sodium phosphate, ammonium phosphate, and potassium phosphate; Feature 5: The acid solution is at least one of sulfuric acid, hydrochloric acid, and nitric acid.
[0015] In one embodiment, step (2) includes at least one of the following features: Feature 6: The alkaline solution is at least one of sodium hydroxide solution and potassium hydroxide solution; Feature 7: The concentration of the alkaline solution is 1.0-2.0 mol / L; Feature 8: The concentration of the N-nitrosophenylammonium solution is 0.2-0.6 mol / L; Feature 9: The N-nitrosophenylammonium solution is added at a molar ratio of iron to N-nitrosophenylammonium of 100:(0.1-3.0); Feature 10: The alkaline solution is added to adjust the pH while stirring, and the stirring speed is 200-350 r / min; Feature 11: The heating refers to raising the temperature to 88-95℃ and then holding it at that temperature for 2-6 hours; Feature 12: The solid phase obtained from the solid-liquid separation is washed with water, dried at 100-120℃ for 2-4 hours, and then calcined once. Feature 13: The temperature of the first calcination is 600°C. 750℃, heating rate is 3 5℃ / min, calcination time is 2 5h.
[0016] In one embodiment, step (3) includes at least one of the following features: Feature 14: The ammonium phosphate solution is obtained by adjusting the pH of a 0.15-0.30 mol / L phosphoric acid solution to 2.0-2.5 with ammonia water, and the calcined material is mixed with the ammonium phosphate solution at a solid-liquid ratio of 80-100 g / L; Feature 15: The soaking temperature is 55-65℃, and the soaking time is 60-90 minutes; Feature 16: The solid phase is washed with water, dried at 100-120℃ for 1-3 hours, and then calcined a second time; Feature 17: The temperature of the secondary calcination is 600°C. 750℃, heating rate is 3 5℃ / min, calcination time is 2 5h.
[0017] In one embodiment, in steps (2) and (3), the oxygen atmosphere is air or oxygen atmosphere.
[0018] The application of a low-density anhydrous iron phosphate as described above in the preparation of lithium iron phosphate cathode materials.
[0019] The beneficial effects of this invention are: (1) The anhydrous iron phosphate of the present invention has a lower density and thinner flaky primary particles, which are easier to grind and can improve the grinding efficiency during subsequent lithium iron phosphate synthesis. (2) The anhydrous iron phosphate of the present invention has a high density and a large specific surface area after grinding, and the lithium iron phosphate cathode material produced subsequently has a higher compaction density and rate performance. (3) The method for preparing anhydrous ferric phosphate of the present invention involves adding N-nitrosophenylammonium during the synthesis of ferric phosphate dihydrate. N-nitrosophenylammonium can form an amorphous flocculent precipitate Fe[C6H5N(O)NO]3 with ferric iron and be mixed in the ferric phosphate dihydrate precipitate to form a coprecipitate. At the same time, N-nitrosophenylammonium can induce directional precipitation of ferric iron, promoting the transformation of primary particles into flakes. When the coprecipitate is calcined, Fe[C6H5N(O)NO]3 decomposes to produce gas and generate iron oxide, leaving more micropores, reducing the particle density of the anhydrous ferric phosphate material, and further destroying the structure of secondary particles, making them easier to grind. By further soaking in ammonium phosphate solution, the generated iron oxide is converted back into ferric phosphate dihydrate and some pores are sealed. During grinding, these pores are still destroyed and exposed, resulting in higher density of the ground particles than before grinding. At the same time, the destroyed pores also generate a larger specific surface area. Attached Figure Description
[0020] Figure 1 This is a SEM image of anhydrous ferric phosphate before grinding in Example 3 of the present invention; Figure 2 This is a SEM image of anhydrous ferric phosphate after grinding in Example 3 of the present invention. Detailed Implementation
[0021] The present invention will be further described below with reference to specific embodiments.
[0022] Example 1: A low-density anhydrous ferric phosphate is composed of secondary particles formed by the agglomeration of primary particles. The secondary particles have a particle size D50 of 2.21 μm, and the primary particles are plate-like with a thickness d of 0.146 μm. The loose bulk density ρ1 of the secondary particles is 0.42 g / cm³, and the specific surface area S1 is 10.31 m². 2 After low-density anhydrous ferric phosphate was ground to a D50' of 0.571 μm, the specific surface area S2 of the obtained material was 12.21 m² / g, and the loose packing density ρ2 of the material was 0.63 g / cm³. Before and after the low-density anhydrous ferric phosphate was ground to a D50' of 0.571 μm, the following relationship was satisfied: K1 is the grinding coefficient; the larger the K1, the easier it is to grind. K2 is the synthesis coefficient. The larger K2 is, the denser the synthesized lithium iron phosphate will be, and the better the rate performance will be. W is the processing coefficient; the larger W is, the easier it is to process into a dense, high-rate lithium iron phosphate cathode material. The grinding method includes the following steps: ① Take 100g of anhydrous ferric phosphate in 4 portions, add 150mL of deionized water to each portion, and mix to make 4 slurries; ② Take 4 portions of 800g zirconium oxide balls with a large ball diameter of 1mm and a small ball diameter of 0.5mm, and a mass ratio of 1:1; ③ The above materials are loaded into the four tanks of a planetary four-cylinder grinder with a motor power of 1.5kW and a capacity of 2L (500mL per tank × 4 tanks); ④ Start the grinder, adjust the speed to 300 r / min, grind for 30 minutes, stop and cool for 10 minutes, repeat 8 times; ⑤ After grinding, separate the zirconia balls to obtain a slurry; ⑥ The slurry is filtered to obtain a solid, which is then dried at 100°C for 2 hours and refilled into the grinding mill along with the zirconia balls; ⑦ Start the grinder, adjust the speed to 200 r / min, grind for 20 min, and then separate to obtain the ground anhydrous ferric phosphate product.
[0023] A method for preparing low-density anhydrous ferric phosphate includes the following steps: Step 1: Mix ferric salt and phosphate according to the iron-phosphorus molar ratio of 1:1.02, and add acid to prepare a phosphorus-iron solution with an iron ion concentration of 0.1 mol / L and a pH of -1.0; the ferric salt is ferric sulfate, the phosphate is sodium phosphate, and the acid is sulfuric acid; Step 2: Prepare a 0.2 mol / L N-nitrosophenylammonium solution; Step 3: Prepare a sodium hydroxide solution with a concentration of 1.0 mol / L; Step 4: Using ferric phosphorus solution as the base liquid, add it to the reaction vessel. Add the sodium hydroxide solution prepared in step 3 to the reaction vessel to adjust the pH of the vessel to 1.8 and control the stirring speed of the vessel to 200 r / min. Step 5: Add the N-nitrosophenylammonium solution prepared in step 2 into the reactor according to the molar ratio of iron to N-nitrosophenylammonium ammonium of 100:0.1; Step 6: Continue stirring, controlling the stirring speed at 200 r / min, and raise the temperature to 88℃, then keep it at that temperature for 2 hours; Step 7: After the reaction is complete, solid-liquid separation is performed. The obtained solid material is washed with pure water and then dried at 100°C for 2 hours to obtain the dried material. Step 8: Calcine the dried material in an air or oxygen atmosphere at a temperature of 600℃, a heating rate of 3℃ / min, and a calcination time of 2h to obtain the calcined material. Step 9: Add the calcined material to the ammonium phosphate solution according to a solid-liquid ratio of 80 g / L, control the temperature at 55℃, and soak for 60 min; the ammonium phosphate solution is obtained by adjusting the pH of a 0.15 mol / L phosphoric acid solution to 2.0 with ammonia water. Step 10: After solid-liquid separation, dry at 100℃ for 1 hour, and then calcine in an air or oxygen atmosphere at a temperature of 600℃, a heating rate of 3℃ / min, and a calcine time of 2 hours to obtain low-density anhydrous iron phosphate material.
[0024] Example 2: A low-density anhydrous ferric phosphate is composed of secondary particles formed by the agglomeration of primary particles. The secondary particles have a particle size D50 of 3.12 μm, and the primary particles are plate-like with a thickness d of 0.122 μm. The loose bulk density ρ1 of the secondary particles is 0.44 g / cm³, and the specific surface area S1 is 7.23 m². 2 / g, after low-density anhydrous ferric phosphate is ground to a D50' of 0.513μm, the specific surface area S2 of the obtained material is 15.43m² / g, and the loose packing density ρ2 of the material is 0.59g / cm³. Before and after the low-density anhydrous ferric phosphate is ground to a D50' of 0.513μm, the following relationship is satisfied: K1 is the grinding coefficient; the larger the K1, the easier it is to grind. K2 is the synthesis coefficient. The larger K2 is, the denser the synthesized lithium iron phosphate will be, and the better the rate performance will be. W is the processing coefficient. The larger W is, the easier it is to process into a dense, high-rate lithium iron phosphate cathode material. The grinding method is the same as in Example 1.
[0025] A method for preparing low-density anhydrous ferric phosphate includes the following steps: Step 1: Mix ferric salt and phosphate according to the iron-phosphorus molar ratio of 1:1.03, and add acid to prepare a phosphorus-iron solution with an iron ion concentration of 0.5 mol / L and a pH of -0.5; the ferric salt is ferric chloride, the phosphate is ammonium phosphate, and the acid is hydrochloric acid; Step 2: Prepare a 0.3 mol / L N-nitrosophenylammonium solution; Step 3: Prepare a sodium hydroxide solution with a concentration of 1.2 mol / L; Step 4: Using ferric phosphorus solution as the base liquid, add it to the reaction vessel. Add the sodium hydroxide solution prepared in step 3 to the reaction vessel to adjust the pH of the vessel to 1.9 and control the stirring speed of the vessel to 240 r / min. Step 5: Add the N-nitrosophenylammonium solution prepared in step 2 into the reactor according to the molar ratio of iron to N-nitrosophenylammonium ammonium of 100:0.5; Step 6: Continue stirring, controlling the stirring speed at 240 rpm, and heat to 90℃, then keep warm for 3 hours; Step 7: After the reaction is complete, solid-liquid separation is performed. The obtained solid material is washed with pure water and then dried at 105℃ for 2.5h to obtain the dried material. Step 8: Calcine the dried material in an air or oxygen atmosphere at a temperature of 630℃, a heating rate of 3.5℃ / min, and a calcination time of 2.5h to obtain the calcined material. Step 9: Add the calcined material to the ammonium phosphate solution according to a solid-liquid ratio of 85 g / L, control the temperature at 58℃, and soak for 65 min; the ammonium phosphate solution is obtained by adjusting the pH of a 0.20 mol / L phosphoric acid solution to 2.1 with ammonia water. Step 10: After solid-liquid separation, dry at 105℃ for 1.5h, and calcine in air or oxygen atmosphere at 630℃, heating rate of 3.5℃ / min, and calcine time of 2.5h to obtain low-density anhydrous iron phosphate material.
[0026] Example 3: A low-density anhydrous ferric phosphate is composed of secondary particles formed by the agglomeration of primary particles. The secondary particles have a particle size D50 of 4.24 μm, and the primary particles are plate-like with a thickness d of 0.101 μm. The loose bulk density ρ1 of the secondary particles is 0.51 g / cm³, and the specific surface area S1 is 5.27 m². 2 / g, its SEM image is as follows Figure 1 As shown, from Figure 1 The image shows secondary particles formed by the agglomeration of primary particles in a flaky shape. After grinding the low-density anhydrous ferric phosphate to a D50' of 0.445 μm, the resulting material has a specific surface area S2 of 18.21 m² / g and a loose packing density ρ2 of 0.56 g / cm³. The SEM image of the ground material is shown below. Figure 2 As shown, the low-density anhydrous ferric phosphate, after being ground to a D50' of 0.445 μm, satisfies the following relationship: K1 is the grinding coefficient; the larger the K1, the easier it is to grind. K2 is the synthesis coefficient. The larger K2 is, the denser the synthesized lithium iron phosphate will be, and the better the rate performance will be. W is the processing coefficient. The larger W is, the easier it is to process into a dense, high-rate lithium iron phosphate cathode material. The grinding method is the same as in Example 1.
[0027] A method for preparing low-density anhydrous ferric phosphate includes the following steps: Step 1: Mix ferric salt and phosphate according to the iron-phosphorus molar ratio of 1:1.03, and add acid to prepare a phosphorus-iron solution with an iron ion concentration of 1.0 mol / L and a pH of 0; the ferric salt is ferric nitrate, the phosphate is potassium phosphate, and the acid is nitric acid; Step 2: Prepare a 0.3 mol / L N-nitrosophenylammonium solution; Step 3: Prepare a sodium hydroxide solution with a concentration of 1.5 mol / L; Step 4: Using ferric phosphorus solution as the base liquid, add it to the reaction vessel. Add the sodium hydroxide solution prepared in step 3 to the reaction vessel, adjust the pH of the vessel to 2.0, and control the stirring speed of the vessel to 280 r / min. Step 5: Add the N-nitrosophenylammonium solution prepared in step 2 into the reactor according to the molar ratio of iron to N-nitrosophenylammonium ammonium of 100:1.0; Step 6: Continue stirring, controlling the stirring speed at 280 rpm, and heat to 90℃, then keep warm for 4 hours; Step 7: After the reaction is complete, solid-liquid separation is performed. The obtained solid material is washed with pure water and then dried at 110°C for 3 hours to obtain the dried material. Step 8: Calcine the dried material in an air or oxygen atmosphere at a temperature of 650℃, a heating rate of 4℃ / min, and a calcination time of 3h to obtain the calcined material. Step 9: Add the calcined material to the ammonium phosphate solution according to a solid-liquid ratio of 90 g / L, control the temperature at 60℃, and soak for 70 min; the ammonium phosphate solution is obtained by adjusting the pH of a 0.22 mol / L phosphoric acid solution to 2.2 with ammonia water. Step 10: After solid-liquid separation, dry at 110℃ for 2 hours, and then calcine in an air or oxygen atmosphere at a temperature of 650℃, a heating rate of 4℃ / min, and a calcination time of 3 hours to obtain low-density anhydrous iron phosphate material.
[0028] Example 4: A low-density anhydrous ferric phosphate is composed of secondary particles formed by the agglomeration of primary particles. The secondary particles have a particle size D50 of 6.13 μm, and the primary particles are plate-like with a thickness d of 0.091 μm. The loose bulk density ρ1 of the secondary particles is 0.57 g / cm³, and the specific surface area S1 is 3.89 m². 2 / g, after low-density anhydrous ferric phosphate is ground to a D50' of 0.476μm, the specific surface area S2 of the obtained material is 19.32m² / g, and the loose packing density ρ2 of the material is 0.54g / cm³. Before and after the low-density anhydrous ferric phosphate is ground to a D50' of 0.476μm, the following relationship is satisfied: K1 is the grinding coefficient; the larger the K1, the easier it is to grind. K2 is the synthesis coefficient. The larger K2 is, the denser the synthesized lithium iron phosphate will be, and the better the rate performance will be. W is the processing coefficient. The larger W is, the easier it is to process into a dense, high-rate lithium iron phosphate cathode material. The grinding method is the same as in Example 1.
[0029] A method for preparing low-density anhydrous ferric phosphate includes the following steps: Step 1: Mix ferric salt and phosphate according to the iron-phosphorus molar ratio of 1:1.04, and add acid to prepare a phosphorus-iron solution with an iron ion concentration of 1.5 mol / L and a pH of 0.5; the ferric salt is ferric sulfate, the phosphate is sodium phosphate, and the acid is sulfuric acid; Step 2: Prepare a 0.4 mol / L N-nitrosophenylammonium solution; Step 3: Prepare a sodium hydroxide solution with a concentration of 1.8 mol / L; Step 4: Using ferric phosphorus solution as the base liquid, add it to the reaction vessel. Add the sodium hydroxide solution prepared in step 3 to the reaction vessel, adjust the pH of the vessel to 2.1, and control the stirring speed of the vessel to 300 r / min. Step 5: Add the N-nitrosophenylammonium solution prepared in step 2 into the reactor according to the molar ratio of iron to N-nitrosophenylammonium ammonium of 100:1.5; Step 6: Continue stirring, controlling the stirring speed at 300 rpm, and heat to 92℃, then keep warm for 5 hours; Step 7: After the reaction is complete, solid-liquid separation is performed. The obtained solid material is washed with pure water and then dried at 115°C for 3 hours to obtain the dried material. Step 8: Calcine the dried material in an air or oxygen atmosphere at a temperature of 680℃, a heating rate of 5℃ / min, and a calcination time of 4h to obtain the calcined material. Step 9: Add the calcined material to the ammonium phosphate solution according to a solid-liquid ratio of 95 g / L, control the temperature at 62℃, and soak for 80 min; the ammonium phosphate solution is a 0.25 mol / L phosphoric acid solution with pH adjusted to 2.3 by ammonia water. Step 10: After solid-liquid separation, dry at 115℃ for 2.5h, and calcine in air or oxygen atmosphere at 680℃, heating rate of 5℃ / min, and calcine time of 4h to obtain low-density anhydrous iron phosphate material.
[0030] Example 5: A low-density anhydrous ferric phosphate is composed of secondary particles formed by the agglomeration of primary particles. The secondary particles have a particle size D50 of 7.91 μm, and the primary particles are plate-like with a thickness d of 0.073 μm. The loose bulk density ρ1 of the secondary particles is 0.63 g / cm³, and the specific surface area S1 is 3.02 m². 2 / g, after low-density anhydrous ferric phosphate is ground to a D50' of 0.429μm, the specific surface area S2 of the obtained material is 20.01m² / g, and the loose packing density ρ2 of the material is 0.48g / cm³. Before and after the low-density anhydrous ferric phosphate is ground to a D50' of 0.429μm, the following relationship is satisfied: K1 is the grinding coefficient; the larger the K1, the easier it is to grind. K2 is the synthesis coefficient. The larger K2 is, the denser the synthesized lithium iron phosphate will be, and the better the rate performance will be. W is the processing coefficient. The larger W is, the easier it is to process into a dense, high-rate lithium iron phosphate cathode material. The grinding method is the same as in Example 1.
[0031] A method for preparing low-density anhydrous ferric phosphate includes the following steps: Step 1: Mix ferric salt and phosphate according to the iron-phosphorus molar ratio of 1:1.05, and add acid to prepare a phosphorus-iron solution with an iron ion concentration of 1.8 mol / L and a pH of 0.5; the ferric salt is ferric sulfate, the phosphate is sodium phosphate, and the acid is sulfuric acid; Step 2: Prepare a 0.5 mol / L N-nitrosophenylammonium solution; Step 3: Prepare a sodium hydroxide solution with a concentration of 1.9 mol / L; Step 4: Using ferric phosphorus solution as the base liquid, add it to the reaction vessel. Add the sodium hydroxide solution prepared in step 3 to the reaction vessel to adjust the pH of the vessel to 2.2 and control the stirring speed of the vessel to 330 r / min. Step 5: Add the N-nitrosophenylammonium solution prepared in step 2 into the reactor according to the molar ratio of iron to N-nitrosophenylammonium ammonium of 100:2.0; Step 6: Continue stirring, controlling the stirring speed at 330 rpm, and heat to 95℃, then keep warm for 6 hours; Step 7: After the reaction is complete, solid-liquid separation is performed. The obtained solid material is washed with pure water and then dried at 120°C for 4 hours to obtain the dried material. Step 8: Calcine the dried material in an air or oxygen atmosphere at a temperature of 700℃, a heating rate of 5℃ / min, and a calcination time of 5h to obtain the calcined material. Step 9: Add the calcined material to the ammonium phosphate solution according to a solid-liquid ratio of 100 g / L, control the temperature at 65℃, and soak for 90 min; the ammonium phosphate solution is a 0.30 mol / L phosphoric acid solution with pH adjusted to 2.4 by ammonia water. Step 10: After solid-liquid separation, dry at 120℃ for 3 hours, and then calcine in an air or oxygen atmosphere at a temperature of 700℃, a heating rate of 5℃ / min, and a calcine time of 5 hours to obtain low-density anhydrous iron phosphate material.
[0032] Example 6: A low-density anhydrous ferric phosphate is composed of secondary particles formed by the agglomeration of primary particles. The secondary particles have a particle size D50 of 9.56 μm, and the primary particles are plate-like with a thickness d of 0.054 μm. The loose bulk density ρ1 of the secondary particles is 0.68 g / cm³, and the specific surface area S1 is 2.43 m². 2 After low-density anhydrous ferric phosphate was ground to a D50' of 0.411 μm, the specific surface area S2 of the obtained material was 21.43 m² / g, and the loose packing density ρ2 of the material was 0.46 g / cm³. Before and after the low-density anhydrous ferric phosphate was ground to a D50' of 0.411 μm, the following relationship was satisfied: K1 is the grinding coefficient; the larger the K1, the easier it is to grind. K2 is the synthesis coefficient. The larger K2 is, the denser the synthesized lithium iron phosphate will be, and the better the rate performance will be. W is the processing coefficient. The larger W is, the easier it is to process into a dense, high-rate lithium iron phosphate cathode material. The grinding method is the same as in Example 1.
[0033] A method for preparing low-density anhydrous ferric phosphate includes the following steps: Step 1: Mix ferric salt and phosphate according to the iron-phosphorus molar ratio of 1:1.05, and add acid to prepare a phosphorus-iron solution with an iron ion concentration of 2.0 mol / L and a pH of 0.5; the ferric salt is ferric chloride, the phosphate is potassium phosphate, and the acid is hydrochloric acid; Step 2: Prepare a 0.6 mol / L N-nitrosophenylammonium solution; Step 3: Prepare a sodium hydroxide solution with a concentration of 2.0 mol / L; Step 4: Using ferric phosphorus solution as the base liquid, add it to the reaction vessel. Add the sodium hydroxide solution prepared in step 3 to the reaction vessel, adjust the pH of the vessel to 2.2, and control the stirring speed of the vessel to 350 r / min. Step 5: Add the N-nitrosophenylammonium solution prepared in step 2 into the reactor according to the molar ratio of iron to N-nitrosophenylammonium ammonium of 100:3.0; Step 6: Continue stirring, controlling the stirring speed at 350 rpm, and heat to 95℃, then keep warm for 6 hours; Step 7: After the reaction is complete, solid-liquid separation is performed. The obtained solid material is washed with pure water and then dried at 120°C for 2 hours to obtain the dried material. Step 8: Calcine the dried material in an air or oxygen atmosphere at a temperature of 750℃, a heating rate of 5℃ / min, and a calcination time of 5h to obtain the calcined material. Step 9: Add the calcined material to the ammonium phosphate solution according to a solid-liquid ratio of 100 g / L, control the temperature at 65℃, and soak for 90 min; the ammonium phosphate solution is obtained by adjusting the pH of a 0.30 mol / L phosphoric acid solution to 2.5 with ammonia water. Step 10: After solid-liquid separation, dry at 120℃ for 3 hours, and then calcine in an air or oxygen atmosphere at a temperature of 750℃, a heating rate of 5℃ / min, and a calcine time of 5 hours to obtain low-density anhydrous iron phosphate material.
[0034] Comparative Example 1: An anhydrous ferric phosphate is a secondary particle formed by the agglomeration of primary particles. The secondary particle size D50 is 4.48 μm; the thickness d of the primary particles is 0.175 μm; the loose packing density ρ1 of the secondary particles is 0.61 g / cm³; and the specific surface area S1 is 4.61 m². 2 / g, after anhydrous ferric phosphate was ground using the same grinding method as in Example 3 to obtain particles with a D50' of 0.862μm, the specific surface area S2 of the obtained material was 8.73m² / g, and the loose packing density ρ2 of the material was 0.72g / cm³. Before and after anhydrous ferric phosphate was ground to a D50' of 0.862μm, the following relationship was satisfied: K1 is the grinding coefficient; the larger the K1, the easier it is to grind. K2 is the synthesis coefficient. The larger K2 is, the denser the synthesized lithium iron phosphate will be, and the better the rate performance will be. W is the processing coefficient. The larger the W, the easier it is to process into a dense, high-rate lithium iron phosphate cathode material.
[0035] The preparation method of Comparative Example 1 differs from that of Example 3 in that N-nitrosophenylammonium solution was not added, and iron oxide conversion was not performed.
[0036] A method for preparing anhydrous iron phosphate material includes the following steps: Step 1: Mix ferric salt and phosphate according to the iron-phosphorus molar ratio of 1:1.03, and add acid to prepare a phosphorus-iron solution with an iron ion concentration of 1.0 mol / L and a pH of 0; the ferric salt is ferric nitrate, the phosphate is potassium phosphate, and the acid is nitric acid; Step 2: Prepare a sodium hydroxide solution with a concentration of 1.5 mol / L; Step 3: Using ferric phosphorus solution as the base liquid, add it to the reaction vessel. Add the sodium hydroxide solution prepared in step 3 to the reaction vessel, adjust the pH of the vessel to 2.0, and control the stirring speed of the vessel to 280 r / min. Step 4: Continue stirring, controlling the stirring speed at 280 rpm, and heat to 90℃, then keep warm for 4 hours; Step 5: After the reaction is complete, solid-liquid separation is performed. The obtained solid material is washed with pure water and then dried at 110℃ for 3 hours to obtain the dried material. Step 6: Calcine the dried material in an air or oxygen atmosphere at a temperature of 650℃, a heating rate of 4℃ / min, and a calcination time of 3h to obtain anhydrous iron phosphate material.
[0037] Comparative Example 2: An anhydrous ferric phosphate is a secondary particle formed by the agglomeration of primary particles. The secondary particle size D50 is 4.37 μm; the thickness d of the primary particles is 0.106 μm; the loose bulk density ρ1 of the secondary particles is 0.52 g / cm³; and the specific surface area S1 is 8.69 m². 2 / g, after anhydrous ferric phosphate was ground using the same grinding method as in Example 3 to obtain particles with a D50' of 0.466μm, the specific surface area S2 of the obtained material was 14.13m² / g, and the loose packing density ρ2 of the material was 0.49g / cm³. Before and after anhydrous ferric phosphate was ground to a D50' of 0.466μm, the following relationship was satisfied: K1 is the grinding coefficient; the larger the K1, the easier it is to grind. K2 is the synthesis coefficient. The larger K2 is, the denser the synthesized lithium iron phosphate will be, and the better the rate performance will be. W is the processing coefficient. The larger the W, the easier it is to process into a dense, high-rate lithium iron phosphate cathode material.
[0038] The difference between the preparation method of Comparative Example 2 and Example 3 is that iron oxide conversion was not performed and steps 9-10 were omitted. A method for preparing anhydrous iron phosphate material includes the following steps: Step 1: Mix ferric salt and phosphate according to the iron-phosphorus molar ratio of 1:1.03, and add acid to prepare a phosphorus-iron solution with an iron ion concentration of 1.0 mol / L and a pH of 0; the ferric salt is ferric nitrate, the phosphate is potassium phosphate, and the acid is nitric acid; Step 2: Prepare a 0.3 mol / L N-nitrosophenylammonium solution; Step 3: Prepare a sodium hydroxide solution with a concentration of 1.5 mol / L; Step 4: Using ferric phosphorus solution as the base liquid, add it to the reaction vessel. Add the sodium hydroxide solution prepared in step 3 to the reaction vessel, adjust the pH of the vessel to 2.0, and control the stirring speed of the vessel to 280 r / min. Step 5: Add the N-nitrosophenylammonium solution prepared in step 2 into the reactor according to the molar ratio of iron to N-nitrosophenylammonium ammonium of 100:1.0; Step 6: Continue stirring, controlling the stirring speed at 280 rpm, and heat to 90℃, then keep warm for 4 hours; Step 7: After the reaction is complete, solid-liquid separation is performed. The obtained solid material is washed with pure water and then dried at 110°C for 3 hours to obtain the dried material. Step 8: Calcine the dried material in an air or oxygen atmosphere at a temperature of 650℃, a heating rate of 4℃ / min, and a calcination time of 3h to obtain anhydrous iron phosphate material.
[0039] The anhydrous ferric phosphate obtained in Examples 1-6 and Comparative Examples 1-2 was tested, and the test results are shown in Table 1 below.
[0040] Test method: ① Particle size determination: The particle size distribution Dv50 of the material was measured using a Malvern 3000 particle size analyzer after internal ultrasonic dispersion for 5 min. ② Primary particle thickness measurement: The surface direct measurement method using scanning electron microscopy (SEM) is preferred (the standard method of T / CI946-2025 is preferred). ③ Loose packing density determination: The loose packing density shall be determined in accordance with GB / T31057.1-2014 "Physical properties testing of granular materials - Part 1: Measurement of loose packing density"; ④ Specific surface area determination: The determination shall be carried out in accordance with GB / T19587-2017 "Determination of specific surface area of solid substances by gas adsorption BET method"; ⑤ Compacted density determination: The compacted density was determined according to GB / T44330-2024 "Determination of compacted density of lithium-ion battery cathode material powder" under a pressure of 3t.
[0041] Table 1.
[0042] As shown in Table 1, the anhydrous ferric phosphate of the present invention has a D50 of 2-10 μm before grinding, and the thickness d of the primary particles is 0.05-0.15 μm; the density ρ1 of the secondary particles is 0.4-0.7 g / cm³, and the specific surface area S1 is 2.0-10.5 m³ / g; the overall density is relatively low, and the flaky primary particles are thin and easy to grind. After grinding to a D50' of 0.4-0.6 μm, the specific surface area S2 of the obtained material is 12-22 m² / g, and the density ρ2 of the material is 0.45-0.75 g / cm³. The ground material has a high density and a large specific surface area.
[0043] In Examples 1-6, as the amount of N-nitrosophenylammonium increases, the thickness of the primary particles gradually decreases, the primary particles are refined, the internal pores of the particles increase, the loose packing density gradually decreases, the particles become less dense, and K1 gradually increases, indicating that the material is easier to grind. However, after grinding, the particle size of the material is smaller, the loose packing density decreases, and the particles become less dense, indicating that the material is less suitable for preparing lithium iron phosphate cathodes.
[0044] Comparing Example 3 with Comparative Example 1, it can be seen that when N-nitrosophenylammonium solution is not added during the preparation process and iron oxide conversion is not carried out, the primary particle thickness of the anhydrous iron phosphate prepared is significantly thicker and exhibits higher density, making it difficult to grind. Under the same conditions, the particle size of the material obtained after grinding is also larger and the specific surface area is lower.
[0045] Comparing Example 3 and Comparative Example 2, it can be seen that when iron oxide conversion is not carried out during the preparation process, the anhydrous iron phosphate prepared will have a higher density, and the density of the material obtained after grinding under the same grinding conditions is poor, between that of Example 3 and Comparative Example 1.
[0046] Experimental example: According to the molar ratio Fe:Li=1:1.1, the materials ground in Examples 1-6 and Comparative Examples 1-2 were mixed with lithium carbonate, and 20% of the total mass of deionized water and 0.3 times the molar amount of iron in glucose were added. After mixing evenly, the mixture was spray-dried. Under the protection of inert gas, it was calcined at 750°C for 15 hours and then naturally cooled to room temperature to obtain the finished lithium iron phosphate cathode material.
[0047] The compaction density of the prepared lithium iron phosphate cathode material was measured. The resulting lithium iron phosphate cathode material was mixed with PVDF and conductive carbon black at a weight ratio of 90:5:5. N,N-dimethylpyrrolidone was added to prepare a 30% mixed slurry. This slurry was coated onto the surface of an aluminum foil current collector to a thickness of 14 μm. After drying and stamping, the cathode sheet was obtained. An 18 μm PE-based membrane was used as the separator. The electrolyte was a 1 mol / L LiPF6 solution with a solvent ratio of EC:DMC:EMC = 1:1:1 (v / v / v). CR2032 coin cells were assembled in a glove box and subjected to a 2.0 μm incubation period at 25°C. Charge and discharge tests were performed within a voltage range of ~3.8V.
[0048] Table 2.
[0049] Result comparison: As shown in Table 2, the lithium iron phosphate cathode material prepared using the anhydrous iron phosphate of the present invention has a compaction density of ≥2.5 g / cm³, a discharge capacity of ≥161 mAh / g at 0.1C, a discharge capacity of ≥158.5 mAh / g at 0.2C, a discharge capacity of ≥151 mAh / g at 0.5C, a discharge capacity of ≥147 mAh / g at 1C, and a capacity retention rate of ≥98% after 200 cycles at 1C.
[0050] Comparing Example 3 with Comparative Example 1, it can be seen that when N-nitrosophenylammonium solution was not added during the preparation process and iron oxide conversion was not carried out, the material was difficult to grind to a smaller particle size, resulting in a significant decrease in the rate performance of the final lithium iron phosphate cathode material.
[0051] Comparing Example 3 with Comparative Example 2, it can be seen that when iron oxide conversion is not carried out during the preparation process, the iron content is high and it cannot be converted into lithium iron phosphate active material, resulting in low discharge capacity and deteriorated cycle performance.
Claims
1. A low-density anhydrous ferric phosphate, characterized in that: It consists of secondary particles formed by the agglomeration of primary particles. The particle size D50 of the secondary particles is 2-10 μm, and the primary particles are plate-like with a thickness d of 0.05-0.15 μm. The loose bulk density ρ1 of the secondary particles is 0.4-0.7 g / cm³, and the specific surface area S1 is 2.0-10.5 m². 2 / g.
2. The low-density anhydrous ferric phosphate according to claim 1, characterized in that: The low-density anhydrous iron phosphate was ground to a D50' of 0.4-0.6 μm, and the resulting material had a specific surface area S2 of 12-22 m² / g and a loose packing density ρ2 of 0.45-0.75 g / cm³.
3. The low-density anhydrous ferric phosphate according to claim 2, characterized in that: The low-density anhydrous ferric phosphate, before and after grinding, satisfies the following relationship: K1 is the grinding coefficient, with a value ranging from 15.0 to 30.0 m. 2 / g.
4. The low-density anhydrous ferric phosphate according to claim 2, characterized in that: The low-density anhydrous ferric phosphate, before and after grinding, satisfies the following relationship: K2 is the synthesis coefficient, with a value ranging from 7.5 to 11.0 μm. -1 .
5. A low-density anhydrous ferric phosphate according to claim 3 or 4, characterized in that: The low-density anhydrous ferric phosphate, before and after grinding, satisfies the following relationship: W is the processing coefficient, with a value ranging from 70.0 to 115.0 m. 2 / g.
6. A method for preparing low-density anhydrous ferric phosphate as described in any one of claims 1-5, characterized in that: Includes the following steps: (1) Mix ferric salt with phosphate, and then add acid to prepare a ferric phosphate solution with a pH of -1.0 to 0.5; (2) Using the phosphorus iron solution obtained in step (1) as the base liquid, add alkaline solution to adjust the pH to 1.8-2.2, then add N-nitrosophenylammonium solution, and heat to carry out the reaction. Then, separate the solid and liquid, and calcine the obtained solid phase once in an oxygen atmosphere to obtain the calcined material. (3) After mixing and soaking the calcined material obtained in step (2) with ammonium phosphate solution, the solid and liquid are separated, and the obtained solid phase is calcined a second time in an oxygen atmosphere to obtain low-density anhydrous iron phosphate.
7. The method for preparing low-density anhydrous ferric phosphate according to claim 6, characterized in that, Step (1) includes at least one of the following features: Feature 1: The molar ratio of iron to phosphorus in the phosphorus-iron solution is 1:(1.02-1.05); Feature 2: The iron ion concentration in the phosphorus-iron solution is 0.1-2.0 mol / L; Feature 3: The ferric salt is at least one of ferric sulfate, ferric chloride, and ferric nitrate; Feature 4: The phosphate is at least one of sodium phosphate, ammonium phosphate, and potassium phosphate; Feature 5: The acid solution is at least one of sulfuric acid, hydrochloric acid, and nitric acid.
8. The method for preparing low-density anhydrous ferric phosphate according to claim 6, characterized in that, Step (2) includes at least one of the following features: Feature 6: The alkaline solution is at least one of sodium hydroxide solution and potassium hydroxide solution; Feature 7: The concentration of the alkaline solution is 1.0-2.0 mol / L; Feature 8: The concentration of the N-nitrosophenylammonium solution is 0.2-0.6 mol / L; Feature 9: The N-nitrosophenylammonium solution is added at a molar ratio of iron to N-nitrosophenylammonium of 100:(0.1-3.0); feature 10: Add the alkaline solution while stirring to adjust the pH. The stirring speed is 200-350 r / min. Feature 11: The heating refers to raising the temperature to 88-95℃ and then holding it at that temperature for 2-6 hours; Feature 12: The solid phase obtained from the solid-liquid separation is washed with water, dried at 100-120℃ for 2-4 hours, and then calcined once. Feature 13: The temperature of the first calcination is 600°C. 750℃, heating rate is 3 5℃ / min, calcination time is 2 5h.
9. The method for preparing low-density anhydrous ferric phosphate according to claim 6, characterized in that, Step (3) includes at least one of the following features: Feature 14: The ammonium phosphate solution is obtained by adjusting the pH of a 0.15-0.30 mol / L phosphoric acid solution to 2.0-2.5 with ammonia water, and the calcined material is mixed with the ammonium phosphate solution at a solid-liquid ratio of 80-100 g / L; Feature 15: The soaking temperature is 55-65℃, and the soaking time is 60-90 minutes; Feature 16: The solid phase is washed with water, dried at 100-120℃ for 1-3 hours, and then calcined a second time; Feature 17: The temperature of the secondary calcination is 600°C. 750℃, heating rate is 3 5℃ / min, calcination time is 2 5h.
10. The application of a low-density anhydrous iron phosphate according to any one of claims 1-5 in the preparation of lithium iron phosphate cathode materials.